2008
DOI: 10.1080/13557850802035236
|View full text |Cite
|
Sign up to set email alerts
|

What do non-English-speaking patients value in acute care? Cultural competency from the patient's perspective: a qualitative study

Abstract: Because of the specific nature of each patient-provider interaction within its particular social and political environment, culturally competent behaviour in one context may be culturally incompetent in another. We propose a model of cultural empowerment that reflects the phenomenological basis of cultural competence in that cultural competence must be consistently renegotiated with any particular patient in a particular healthcare context. Similarly, ongoing community consultations are needed for health servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 38 publications
2
84
0
2
Order By: Relevance
“…We used the "rapid bilingual appraisal" model (Whelan, 2004) in which focus groups were facilitated by a bilingual/bicultural facilitator while another bilingual/bicultural individual interpreted the proceedings to the non-bilingual principal investigator (PI) in the room. This approach allowed the non-bilingual PI to fully engage in the data collection while ensuring the natural flow of the focus group interview (Garrett, Dickson, Lis-Young, Whelan, & Roberto-Forero, 2008). All focus group proceedings were audiorecorded for analysis.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…We used the "rapid bilingual appraisal" model (Whelan, 2004) in which focus groups were facilitated by a bilingual/bicultural facilitator while another bilingual/bicultural individual interpreted the proceedings to the non-bilingual principal investigator (PI) in the room. This approach allowed the non-bilingual PI to fully engage in the data collection while ensuring the natural flow of the focus group interview (Garrett, Dickson, Lis-Young, Whelan, & Roberto-Forero, 2008). All focus group proceedings were audiorecorded for analysis.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…6 The literature in this area also identifies significant misunderstandings between patients and health professionals 7,8 and issues related to cultural isolation of patients and their families 7 and cultural competence of health professionals. 5 The limited available community-based research in this area suggests that these issues are also problematic for cancer patients from ethnic minority groups being cared for at home. 9,10 Australia, like most other developed nations, is ethnically and culturally diverse.…”
mentioning
confidence: 99%
“…Research into the broader healthcare experiences of immigrants and other ethnic minority groups points to a strong link between ethnicity and communication barriers. 5,6 For example, language barriers have been associated with frustration and feelings of hopelessness among Chinese-Australian women with breast cancer. 6 The literature in this area also identifies significant misunderstandings between patients and health professionals 7,8 and issues related to cultural isolation of patients and their families 7 and cultural competence of health professionals.…”
mentioning
confidence: 99%
“…An alternative approach that allows the nonbilingual researcher's real-time participation is the rapid bilingual appraisal model (Whelan, 2004), in which an interpreter interprets the proceedings to the researcher as the bilingual interviewer collects data. Adapting this model, Garrett, Dickson, Lis-Young, Whelan, and Roberto-Forero (2004) conducted focus groups with several language groups and reported that this approach allowed the nonbilingual researcher to fully engage in data collection while ensuring the natural flow of the focus group interview.…”
Section: Measurementmentioning
confidence: 99%